Perceived Risk-Based Maintenance Management (PRBMM) for public schools: A systematic literature review/ Nurul Diyana Mohd Dahari ... [et al.] - Mohd Dahari, Nurul Diyana; Mohammad Ali, Irwan; Khalil, Natasha; Abdul Wahab, Suriani Ngah (Universiti Teknologi MARA, Perak, 2024)
Perceived risk is important to identify the appropriate improvements needed for maintenance management in public schools. Addressing perceived risk in public schools highlights the importance of considering it to enhance facility performance and sustainability. School building maintenance is a global issue that needs immediate attention, as poor maintenance can compromise a school’s safetyl. This should not undermine the school’s mission of providing quality education to all occupants while ensuring productivity and comfort through effective building maintenance management. This study aims to address the gap in current maintenance management practices by investigating the role of perceived risk in enhancing maintenance management in public schools. The primary objective is to develop a conceptual model based on Perceived Risk-Based Maintenance Management (PRBMM), which prioritizes maintenance tasks according to perceived risk, thereby improving facility performance and sustainability. A systematic literature review was conducted after a comprehensive search of research papers from 2009 to 2024 on perceived risk in risk-based maintenance management. The search included databases such as Scopus, Web of Science (WoS), Elsevier, Google Scholar, and Science Direct using keywords such as (“Perceived Risk”) AND (“Maintenance Management”) and (“Risk-Based Maintenance Management”) and (“Public School”). The searcher identified 1,165 articles based on the search term of 150 articles in Scopus, 200 articles in WoS, 155 articles in Elsevier, 230 articles in Google Scholar, 430 articles in Science Direct, and 1,155 were excluded. This research highlights the necessity of investigating the relationships between perceived risk and Risk-Based Maintenance Management (PRBMM), focusing on responses to PRBMM approaches. As a result, a conceptual model centred on PRBMM is proposed.